Burglars blocked by barriers? The impact of physical and social barriers on residential burglars' target location choices in China. (March 2021) - Xiao, Luzi; Ruiter, Stijn; Liu, Lin; Song, Guangwen; Zhou, Suhong
Abstract: Based on an offender spatial decision-making perspective, this burglary target location choice study aims to understand how physical and social barriers affect why residential burglars commit their crimes at particular locations in a major Chinese city. Using data on 3860 residential burglaries committed by 3772 burglars between January 2012 and June 2016 in ZG city, China, conditional logit (discrete choice) models were estimated to assess residential burglars' target location choice preferences. Three types of physical barriers were distinguished: major roads with access control, major roads without access control, and major rivers. Social barriers were constructed based on the Hukou system to reflect how local and nonlocal residents live segregated lives. Results show that residential burglars are less likely to target areas for which they have to cross a physical barrier and even less likely to do so if they have to cross multiple rivers. Local burglars are more likely to target communities with a majority of local residents than communities with a majority nonlocal population or a mixed community. Such a social barrier was less pronounced for nonlocal burglars. These findings add new insight that physical and social barriers affect, to various degrees, where residential burglars in China commit their crimes. Highlights: This study aims to understand how barriers affect why residential burglars commit their crimes at particular locations in a major Chinese city. All burglars are less likely to target areas separated by rivers and major roads. Local burglars are more likely to target communities with a majority of local residents than the other ones. Such social barrier effect is less pronounced for nonlocal burglars.